Adverbs in Spanish–English code-switching: Comparing verb raising and non-raising - Koronkiewicz, Bryan (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2022)
Aims and objectives/purpose/research questions: Using generative syntactic theory regarding verb raising, predictions are made about adverb position in intra-sentential Spanish–English code-switching. Since both languages allow for non-raising, pre-verbal adverbs should be acceptably switched. However, since verb raising is only available in Spanish, post-verbal adverbs should only be allowed with a Spanish finite verb. Design/methodology/approach: Spanish–English early bilinguals (n = 24) completed a written acceptability judgment task with a 7-point Likert-type scale. The Spanish–English code-switched sentences contained a finite verb switched with a post-verbal or pre-verbal adverb. In addition, comparison sets of monolingual equivalents were tested, targeting adverb order in Spanish and English. Data and analysis: A total of 192 judgments were included in the analysis, and z-scores of the mean ratings provided by the participants were calculated. After a descriptive analysis of the results compared language and adverb order, statistical analyses were conducted via analyses of variance (ANOVAs). Findings/conclusions: Participants showed a preference for non-raising in English, while they accepted both orders in Spanish, but only with adverbs of completion and manner. For code-switching, non-raising was always acceptable, but verb raising varied. The availability of switched non-raising directly follows from the literature. However, the language of the finite verb did not predict availability of verb raising in code-switching. The results suggest that the language of the adverb is crucial to the availability of switching, not solely the verb. Originality: The status of adverbs in code-switching has been left relatively unexplored. This study provides important details regarding adverb position both in mixed Spanish–English utterances and in monolingual contexts for this particular bilingual population. Significance/implications: These findings have a broader impact by providing data about adverb-position preferences in Spanish for a different community of speakers. In particular, it shows even more variability in the idiosyncratic behavior of different adverbs in Spanish.